Vpliv novele ZPP-E na položaj odvetnika v pravdi - Brežan, Bojan (Pravni letopis, 2020)
The article considers the effect of amendment E of the Civil Procedure Act on the position of the party's counsel in a litigation. The amendments to trial preparation are analysed under the assumption that it is the predictability of the process that is key for counsel work. The author finds that the amendment failed to reach this goal, but a greater practical effect of the amendment could nevertheless be achieved should the purpose of its provisions be more consistently honoured. The article also considers certain changes regarding the service of documents and the novelties aimed at improving the parties' position regarding the making of claims and presenting of evidence. It concludes with a brief analysis of the changes in the legal remedies procedures.
Keywords: odvetniki; pravdni postopek; Slovenija; sodišča